Analysis of a-SiCN:H films by X-ray photoelectron spectroscopy. (April 2017) - Peter, S.; Speck, F.; Lindner, M.; Seyller, T.
Abstract: The aim of the present study is to assess the suitability of X-ray photoelectron spectroscopy (XPS) for the precise compositional analysis of μm-thick hydrogenated amorphous silicon carbonitride films (a-SiCN:H) which were deposited by plasma enhanced chemical vapour deposition (PECVD). A first principles data evaluation based on photoionisation cross-sections, electron inelastic mean free paths (IMFPs), angular asymmetry factors and the spectrometer transmission function was performed to determine atomic ratios from XPS peak intensities. The spectrometer transmission function was determined using the so-called bias method. For comparison, the elemental composition in a-SiCN:H films was measured by elastic recoil detection analysis (ERDA) and secondary ion mass spectrometry (SIMS). The atomic ratios of Si, C and N obtained by reference-free XPS agree very well with ERDA elemental composition data (mean deviation 4.7%). Thus, not only the first principles analysis works well, but also sputtering with 2.3 keV Ar + ions at large angles of incidence (scanned beam under 75° to surface normal) made the true a-SiCN:H bulk composition accessible. In addition, the bulk plasmon energy loss in a-SiCN:H was found to change systematically with film composition and it may be used to estimate the hydrogen content in these films. Highlights: Composition of μm-thick a-SiCN:H determined by first principles analysis of XPS spectra. The electron analyser transmission function is determined using the bias method. Very good agreement of element concentration ratios by XPS and ERDA. Bulk plasmon energy correlates with hydrogen content in the films.